TAX AVOIDANCE FIRM LEVEL CHARACTERISTICS: EVIDENCE FROM INDONESIA - Joachim, Hansi (Bina Nusantara University, 2024)
This study examined the tax avoidance characteristics among Indonesian firms. The aim of this study was to provide firm level characteristics of Indonesian public listed companies that conduct tax avoidance, while taking into accounts the scarce literature that studied IFRS adherence and audit quality towards tax avoidance. Five hypotheses were formed to test tax avoidance in Indonesia. Firm size, leverage, last year’s profitability, audit quality and IFRS adherence were selected to serve as the predictors in this research. Using 942 firm year observations from 2019-2021, this study used pooled-sample regression to document that firm size, leverage, and audit quality played a distinct role of tax avoidant companies. Firm size and leverage positively affect tax avoidance. On the other hand, audit quality significantly decrease tax avoidance. Meanwhile, IFRS adherence and profitability had no significant impact on tax avoidance. The contribution of this research was to provide recommendation to Indonesian Tax Authority and auditors to strengthen their controls over financial and tax reporting in Indonesia and provide fresh insights to fellow researchers regarding tax avoidance matters in Indonesia.